2001
DOI: 10.1054/bjoc.2000.1643
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of glomerular filtration rate in cancer patients

Abstract: The frequent need to obtain an estimate of renal function in cancer patients, not least for targeting carboplatin dose, has led to a number of approaches to estimate glomerular filtration rate (GFR). This study aimed to develop a simple and reliable method to estimate GFR using readily-available patient characteristics. Data from 62 patients with estimates of 51 Cr-EDTA clearance were analysed to determine the most appropriate formula relating this method of measuring GFR to patient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 22 publications
(24 reference statements)
3
96
0
2
Order By: Relevance
“…The abilities of these models to predict GFR were compared with the functional form of previously published creatinine clearance models. This type of population pharmacokinetic approach for predicting GFR has previously been used successfully in adults (Martin et al, 1998;Wright et al, 2001) and in children with renal disease (Léger et al, 2002). 51 Cr-EDTA clearance was strongly correlated to body size, with a simple additive model (16.25 þ 1.67 Â Wt) proving to be as good a fit as that obtained using more complex transformations of BSA and weight.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The abilities of these models to predict GFR were compared with the functional form of previously published creatinine clearance models. This type of population pharmacokinetic approach for predicting GFR has previously been used successfully in adults (Martin et al, 1998;Wright et al, 2001) and in children with renal disease (Léger et al, 2002). 51 Cr-EDTA clearance was strongly correlated to body size, with a simple additive model (16.25 þ 1.67 Â Wt) proving to be as good a fit as that obtained using more complex transformations of BSA and weight.…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, approaches based on nonlinear mixed effects models, often referred to as population models, have recently been published and independently assessed (Martin et al, 1998;Wright et al, 2001;Poole et al, 2002;Léger et al, 2002). These methods involve the use of patient specific 51 Cr-EDTA plasma data together with supplementary covariate information.…”
mentioning
confidence: 99%
“…Whereas the CG equation is utilized in most clinical trials, and recognized by the Food and Drug Administration (FDA) in studies of patients with renal impairment, 29 other formulas have been proposed as more applicable for use in cancer patients. 30 For example, in a study of 116 ovarian cancer patients, Calvert et al 31 reported that GFR determined by chromium-51-EDTA clearance had correlation coefficients of 0.75 with the Jelliffe and 0.65 with the CG formula estimates of CrCl. More recently, investigators have called for exploration of the MDRD study equation in oncology trials.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsworth et al studied the performance of the CG and MDRD equations in a larger oncology cohort, as well as investigating the accuracy of the Wright and Jeliffe equations, which were specifically derived from oncology cohorts (21)(22)(23).…”
Section: Effect Of Estimating Gfr On Carboplatin Prescribingmentioning
confidence: 99%